Solutions of nonlinear fractional coupled Hirota-Satsuma-KdV Equation - Cui, Runqing (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
Our interest in the present work is in implementing the FPSM to stress it power in handing the nonlinear fractional coupled Hirota-Satsuma-KdV Equation. The approximate analytical solution of this type equations are obtained.